IN VIVO AND IN VITRO EVALUATION OF TEPHROSIA CALOPHYLLA FOR ANTI-DIABETIC PROPERTIES - C., Ramesh; A., Prameela Rani (International Journal of Pharmacy and Pharmaceutical Sciences, 2018)
Objective: The objective the present work was to investigate in vivo and in vitro anti-diabetic potentials of methanol extract of Tephrosia calophylla against alloxan-induced diabetes in albino rats. Methods: For in vivo evaluation, diabetes was induced in albino rats by administering a single dose of alloxan. The study was designed to test the acute effect of methanol extract of Tephrosia calophylla (TCME) to reduce blood glucose in OGTT. The chronic study of 21 d was performed against diabetic rats and blood glucose was determined at 1st, 7th, 14th and 21st day. In chronic in vivo study, serum concentrations of insulin, urea, creatinine, total cholesterol, triglycerides, ALT and AST were also estimated at 21st day. The in vitro Î±-glucisidase inhibitory activity and Î±-amylase inhibitory activity were performed and IC50 values of the extract was determined. The glucose uptake by rat hemidiaphragm model was also used test potentials of the extract to increase utilization of the glucose by tissues. Results: In OGTT, standard glibenclamide and TCME at 400 mg/kg treated animals have shown significant reduction in blood glucose at 90 min but at 120 min, blood glucose level (BGL) was significantly reduced in glibenclamide and TCME at 200 mg/kg and 400 mg/kg treated animals compared to diabetic control group. In chronic modelthe methanol extract effectively reduced blood glucose levels (P<0.001) at 14 th and 21st day of study in therapeutic groups and effect was comparable to that of standard. The extract could also significantly (P<0.001) reduce concentrations of SGOT, triglycerides (TGs), Total cholesterol (TC) and urea in serum and significantly (P<0.001) increased the insulin level in blood which proves beneficial effects of the extract in diabetes. The change in concentrations of SGPT and urea were less significant (P>0.01). In vitro studies, against both glucosidae and Â amyalase inhibitory activities, extract has shown significant IC50 values and it also enhanced glucose utilization by rat hemidaphragm. Conclusion: The results obtained from the present study suggest that, the methanol extract of Tephrosia calophylla possess significant in vivo anti-diabetic properties against alloxan induced diabetes in rats. The results also suggests that, TCME also possess the significant in vitro anti-dabetic potentials.